Sistem Pembayaran Gaji Karyawan PT. Sawit Sinar Agung Persada Menurut Perspektif Ekonomi Syariah - Ridho Alfarizi; Agustina Mutia; Marissa Putriana (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Salary is a term that we often find in business relationships between employees and companies. The term is a form of remuneration from the company to employees, but with different criteria. We often hear that salaries are used by private or state companies to their permanent employees and are paid within a certain period of time. Employee payroll is a form of compensation given to employees. The compensation is financial in nature and is the main form of compensation available to employees. Because the salary received by employees functions as a support for their survival, namely to fulfill clothing, food, shelter, education and others. In Islamic economics, the determination of workers' wages strongly adheres to the principles of justice and adequacy. The main principle of justice lies in the clarity of the contract (transaction) and commitment on the basis of willingness to do so (from the person in the contract). Contracts in work transactions are contracts that occur between workers and employers, so that before workers are hired, it must be clear how the wages will be received by workers. The wage includes the amount of wages and the procedure for paying wages. Therefore, in an agreement must accommodate workers' payers with the part they should receive according to their work. This study tries to show how the employee salary payment system at PT. Sinar Agung Persada according to the perspective of Islamic economics. The form of this research is field research, is descriptive qualitative, using interviews, documentation, and observation to collect data. In accordance with the DSN MUI Fatwa No.09/DSN-MUI/iv/2000 which stipulates the pillars of Ijarah, the salary payment system at PT. Sinar Agung Persada in Pulau Pandan village in general. In terms of the ijarah requirements, they are not fulfilled, because in the salary payment system for employees of PT. In Sawit Sinar Agung Persada, there is an element of displeasure with employees related to the existence of dependent salaries and contract discrepancies related to the amount of salary paid by the company to employees based on research findings. However, if viewed from a proper perspective, it means that there is enough clothing, food, shelter, payment of salaries for employees of PT. SawitSinar Agung Persada can be said to be feasible, because the basic needs, in the form of clothing, food, boards for the employees are fulfilled with the salary they get in accordance with the sharia economy.